PENGARUH KUALITAS LAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN: STUDI KASUS PELANGGAN ASTRA ISUZU MARGOMULYO SURABAYA - Benedictus Alexyagtus Wangge; Achmad Daengs GS; I Gd Wiyasa (Jurnal Mahasiswa Manajemen dan Akuntansi, 2022)
The aim of this study was to know wether the sevice quality, and promotion to customers satisfaction of Astra Isuzu Margomulyo Surabaya. This search sample amount of 80 respondents using as the sample by Purposive Sampling technique, ( is sampling based on a specific target , while the criteria that will be used is who live in surabaya and have done service at least 2 times in Astra Isuzu Margomulyo Surabaya. Based on the result of the study, it was found the regression equation as follows: Y = 5.757 + 0,306 X1 + 0,490X2+0.4. The most powerful dependent variable was the promotion (0,490) and the last variable quality service that (0.306). The hypothesis testing using t-test showed thatthere is two variable (quality service and promotion) have the positive and statistically significant impact to the dependent variable customer satisfaction. Figures adjusted R square of 0,528 indicates that 52.8 percent of the customer satisfaction could be explained by quality service and promotion variables, meanwhile 47.2 percent of the rest were the impact of the other variable which not examined in this study.